A case study on peer relationships between children with and without autism spectrum disorder in a Chinese inclusive kindergarten. Issue 2 (June 2023) - Xie, Zhengli; Deng, Meng; Yuan, Jingyu
The development of sustainable early childhood education advocates for the holistic development of all children, including children with autism spectrum disorder (ASD). As an important indicator of children's social development, peer relationships between children with and without ASD in inclusive kindergarten have not gained much attention. Adopting peer nomination, semi-structured interviews, and participant observations, this study described peer relationships between the two types of children in a Chinese inclusive kindergarten and explored its influential factors. Fourteen children with ASD, 12 children without ASD, 4 teachers, the principal of the kindergarten, and 4 parents of children with ASD participated in this study. The results indicated three types of peer relationships: rejected, neglected, and average. ASD children's emotional and behavioral challenges, their limited social interaction skills, and teachers' positive feedback on children with ASD were the major reasons for being labeled the above three types respectively. Furthermore, three protective factors (the rule of child pairing in the kindergarten, innovative curriculum and instructional design, and assistance from parents of ASD children) and three hindering factors (hierarchical roles of the children, the dominance of the medical model, and lack of professional knowledge and skills) of children's peer relationships were identified. Implications and limitations are discussed.